2020
DOI: 10.1002/cpt.2018
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miRNAs as Biomarkers for CYP2B6 Enzyme Activity

Abstract: The CYP2B6 gene is highly polymorphic and its activity shows wide interindividual variability. However, substantial variability in CYP2B6 activity remains unexplained by the known CYP2B6 genetic variations. Circulating, cell‐free micro RNAs (miRNAs) may serve as biomarkers of hepatic enzyme activity. CYP2B6 activity in 72 healthy volunteers was determined using the disposition of efavirenz as a probe drug. Circulating miRNA expression was quantified from baseline plasma samples. A linear model consisting of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…A recent study by Zastrozhin et al found a significant negative correlation between CYP3A activity measured by urinary 6 β -hydroxycortisol/cortisol ratio and the plasma concentration of miR-27b in patients taking the CYP3A substrate alprazolam ( Zastrozhin et al, 2020 ). Another study developed a linear regression model to predict CYP2B6 activity, as measured by metabolism of the probe substrate efavirenz, in 72 healthy volunteers ( Ipe et al, 2021 ). Researchers found that the addition of seven circulating miRNAs (miR-204–5p, miR-212–3p, miR-3649, miR-3941, miR-4254, miR-4442, and miR-6867– 5p) to a linear regression model accounting for CYP2B6 genotype-determined metabolizer status, age, sex, and race increased the predictive power of their model from approximately 8% to 45% ( Ipe et al, 2021 ).…”
Section: Circulating Ncrnasmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Zastrozhin et al found a significant negative correlation between CYP3A activity measured by urinary 6 β -hydroxycortisol/cortisol ratio and the plasma concentration of miR-27b in patients taking the CYP3A substrate alprazolam ( Zastrozhin et al, 2020 ). Another study developed a linear regression model to predict CYP2B6 activity, as measured by metabolism of the probe substrate efavirenz, in 72 healthy volunteers ( Ipe et al, 2021 ). Researchers found that the addition of seven circulating miRNAs (miR-204–5p, miR-212–3p, miR-3649, miR-3941, miR-4254, miR-4442, and miR-6867– 5p) to a linear regression model accounting for CYP2B6 genotype-determined metabolizer status, age, sex, and race increased the predictive power of their model from approximately 8% to 45% ( Ipe et al, 2021 ).…”
Section: Circulating Ncrnasmentioning
confidence: 99%
“…Another study developed a linear regression model to predict CYP2B6 activity, as measured by metabolism of the probe substrate efavirenz, in 72 healthy volunteers ( Ipe et al, 2021 ). Researchers found that the addition of seven circulating miRNAs (miR-204–5p, miR-212–3p, miR-3649, miR-3941, miR-4254, miR-4442, and miR-6867– 5p) to a linear regression model accounting for CYP2B6 genotype-determined metabolizer status, age, sex, and race increased the predictive power of their model from approximately 8% to 45% ( Ipe et al, 2021 ). Expression of phase II enzymes, including sulfotransferases (SULTs) and UDP-glucuronosyltransferases (UGTs), are also modulated by ncRNAs ( Yu et al, 2010 ; Li et al, 2020 ; Hu et al, 2022 ).…”
Section: Circulating Ncrnasmentioning
confidence: 99%
“…By using the multivariate adaptive regression splines ML method, Hall et al were able to identify the influence of weight and/or age on the PK of dapsone, not identifiable with standard population PK approaches as occurring only between certain ranges of patients' covariates, delimited by multiple regions of discontinuity (66). In another example, a reverse translational analysis using supervised-feature selection identified a circulating 7-miRNA signature as a predictor of population variability in CYP2B6 activity based on screening of expression of 2510 miRNAs in a multi-dimensional covariate analysis of efavirenz PK (67). The incorporation of big data and ML into the PMX pipeline to enhance the structural, population, and covariate modeling processes (Fig.…”
Section: Dosementioning
confidence: 99%